One more step in solving the Chydorus puzzle—a morphological comparison between Chydorus tilhoi Rey & Saint-Jeans, 1969 and Chydorus sphaericus (O.F. Müller, 1776) (Crustacea: Cladocera) - Sousa, Francisco Diogo Rocha; Silva, Barbara Aparecida Souza Da; Elmoor-Loureiro, Lourdes M. A.; Moreira-Silva, Camila; Espolau, Greyce; Sarmento, Hugo; Isumbisho, Mwapu; Borges, Alberto V.; Perbiche-Neves, Gilmar (Zootaxa, 2024)
A number of species of Chydorus Leach, 1816 (Crustacea: Cladocera) need improvements in their taxonomy much more than any other genus within the family Chydoridae Dybowsky & Grochowski, 1894 emend. Frey, 1967, which makes the systematics of the genus still a puzzle that lacks several pieces. Here, we redescribe the African species Chydorus tilhoi Rey & Saint-Jeans, 1969 and compare its morphology with that of Chydorus sphaericus (O.F. Müller, 1776). The two taxa might be easily differentiated because C. tilhoi has a single and relatively large major head pore with a wide rim, labral keel elongated with a large spine, and postabdomen with postanal part elongated, narrowing distally and with denticles near its anal margin, organized in groups. These morphological traits are absent in C. sphaericus. Chydorus tilhoi and C. sphaericus also differ in the morphology of the first (Inner Distal Lobe setae), third (exopodite proportion), and fifth (exopodite shape) limbs. Based on the literature and our observations, the limb morphology of C. tilhoi has important similarities with that of C. breviceps, C. nitidulus and C. dentifer, and their translocation to a new genus seems to be a fundamental piece in the puzzle of Chydorus.